Rancang Bangun Simulator Pengenalan Suara Ucapan untuk Gerakan Mesin CNC - Herry Sujaini; Arif Bijaksana PN. (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2004)
This research target is to develop a simulator program to arrange the movement ofmachine CNC932, where the command conducted by speech. Examination conducted to seethe ability of system to translate of speech input for the movement commands of machineCNC932. Attempt to simulator done by giving 7 available commands conducted by 3 peopletester as much each 20 times.Before doing attempt tester trained their voice to program. Commands given by testerpass the microphone consisted of "kiri", "kanan", "maju", "mundur", "naik", "turun", " stop"and "bor”.Result of examination to simulator developed to be got to every command given getthe above efficacy level 85%. Command owning highest efficacy level is "maju" equal to96,7%, while command own the level of lowest efficacy is “kiri" equal to 88,3%.Keywords: simulator, speech, CNC932